The Dual Role of Employee Engagement in the Relationship Between Workplace Flexibility, Skill Development, and Retention - Kusumah, Alum; Sulistyandari; Lee, Cheng-Wen (Universitas Brawijaya, Indonesia, 2025)
Employee retention constitutes a pressing concern for nonprofit institutions operating under resource-constrained conditions, as reflected in recent studies of developing economies such as Indonesia. This study, therefore, investigates how workplace flexibility and professional skill cultivation influence retention within Indonesian Islamic philanthropy, incorporating employee engagement as both mediator and moderator. This study employed partial least squares structural equation modeling (PLS-SEM) with a comprehensive dataset of 207 Lazismu employees. The findings demonstrate that skill development exerts a stronger direct relationship with retention than workplace flexibility, while both practices simultaneously elevate engagement. Engagement is a two-way process, as it filters the impact of organizational practices on retention while also moderating the size of these impacts, thereby forming a self-reinforcing environment of commitment. Placing the results in the context of the Job Demands-Resources theory, while considering the importance of Islamic values and institutional realities, the study highlights the necessity of planning training interventions in line with intrinsic motivation and incorporating the flexibility of work structures to increase the stability of a mission-driven workforce.